Stress Levels Affect the Quality of Life of Elderly People with Hypertension in Panti Werdha - Christy Wattimena; Dwi Astuti; Theresie Chindyana Herman (Universitas Tribhuwana Tunggadewi, 2025)
Stress is the most common psychological disorder experienced by the elderly and has a significant impact on their quality of life. One of the triggers of stress in the elderly is non-communicable diseases such as hypertension. This study aims to determine the relationship between stress levels to the quality of life of elderly people with hypertension. The research method used is quantitative correlational with a sample size of 40 elderly people with hypertension at the Tat Twan Asi Pos 7 Sentani Nursing Home, Jayapura. The sampling technique used total sampling with a purposive sampling approach. The inclusion criteria included willingness to be a respondent, consumption of at least one type of antihypertensive drug, full consciousness, and the ability to be interviewed in Indonesian. The exclusion criteria were elderly people who experienced disorientation while the exclusion criteria were the elderly who experienced disorientation of time, place, and people. The instruments used were the DASS-42 and WHOQOL-BREF questionnaires. Data analysis was performed univariately and bivariately using the Spearman test with the assistance of SPSS 27 for Windows 11. The results showed a significant relationship between stress levels and the quality of life of elderly people with hypertension (p=0.001). Most elderly people experienced severe stress and low quality of life. Therefore, a comprehensive approach is needed, taking into account other risk factors such as symptoms of depression and anxiety experienced by the elderly, to make health interventions more effective.